PEMBELAJARAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN METODE MULTISENSORI PADA SISWA KELAS X SMA PASUNDAN BANJARAN KABUPATEN BANDUNG - Nanang Maulana (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
This study aims to investigate the effectiveness of multisensory teaching method in learning writing narrative text at class X students of SMA Pasundan Banjaran, Bandung regency. In this research, the researcher used one of quantitive research methods, namely quasi experimental by using literature review, trials, test, assessment technique analysis as research design. The findings shows that multisensory teaching method is appropriate method to teach writing narrative text. It proven from results of statictically assessment with significancy different of two mean between pre-test and post-test. The post-test score is tcount 16.52 > ttable 2.04 at significancy level 0.05 with 24 degrees of freedom. It means, learning writing narrative text by using multisensory teaching method in learning writing narrative text at class X students of SMA Pasundan Banjaran, Bandung regency is good. So that, the researcher concludes that multisensory teaching method is appropriate to use in teaching writing narrative text.